Art in the archaeological imagination - Gheorghiu, Dragos (Oxbow Books, 2020)
The present volume shows the archaeological thinking as a form of art, revealing the poetics of the archaeological imagination. It shows that, in their work, archaeologists, without being inspired by contemporary artists, use creative methods, and their analysis of the art of the past goes beyond the material culture of the art objects, into the realm of the mental processes of creation.0Consequently, the purpose of this book is to present the archaeological research functioning as a sort of artistic creation, proposing new perspectives on the archaeological imagination. It offers an exploration of the creative processes, the possibility of finding inspiration in experientiality, and the approach to the act of creation as a subject for archaeological research.0When analysing the art of the past, or when using art methods to approach the past, we are facing an act of creation where imagination, emotion, and creativity combine under the form of an experiential instrument of investigation.0The book offers a vision of archaeological research, a means to understand the complexity of the human nature, and consequently, to approach the human thinking structured on similarity and symbolism, being able to detect cultural and psychological subjects ignored until today, and, at the same time, to offer a series of visions of art, seen from the perspective of archaeology.